Avaliação de políticas públicas com base na sustentabilidade: um estudo de caso sobre o projeto costurando o futuro no município de Fortaleza/CE - Rêgo, Nadyegida Barbosa do (2023)
The aim of this study was to evaluate the implementation of the Stitching the Future Project and its impact as a public policy, focusing on the experience of the Bom Jardim workshop in Fortaleza, according to sustainability indicators. The Stitching the Future Project is a productive inclusion policy of the Municipal Secretariat for Economic Development (SDE) of the Fortaleza City Council (PMF). The author of this research took part in the project's implementation process in 2021, monitoring the implementation of the policy in eight workshops, including Ateliê do Bom Jardim, and in 2023 she left the PMF. This research is situated in the socioeconomic context experienced by 15 (fifteen) women living in the Bom Jardim neighborhood. The aim of the project studied is to provide professional training for insertion and reinsertion into the world of work, through the use of collaborative spaces in PMF facilities, promoting the socio-productive inclusion of people who are in a situation of financial vulnerability, as well as strengthening the local economy. Methodologically, the research is qualitative in nature, and the data collection procedures followed the triangulation of data based on bibliographical and documentary research and interviews, while the data analysis followed the perspective of Sustainability-Based Public Policy Evaluation (SPE). The structuring of the text begins with reflections on the link between the environmental, social and economic spheres, understanding the dynamics at a global level that have repercussions for the local level, bringing in international legal issues, theoretical aspects of productive inclusion, circular economy and sustainable development. Next, we look at public policies as instruments for promoting rights, highlighting the issue of gender, especially women's rights, and we look at the Stitching the Future Project as a case study due to the socio-economic context of the beneficiary communities, with the Bom Jardim neighborhood being chosen due to its level of vulnerability and the significant participation of women. Finally, the results and discussion of the application of Sustainability-Based Public Policy Evaluation (SPE) in the Stitching the Future Project are described. In relation to the intended objectives, it was found that the implementation of the project contributed to reduce some of the vulnerability experienced by women in the Bom Jardim neighborhood on a larger scale than the promotion of productive inclusion itself, with women's empowerment being perceived from the activities developed and the results obtained, considering the length of time the public policy has been implemented. The conclusion is that, although there are positive effects in the mentioned project, in the four dimensions of SPE involving social participation, minimizing damage to nature, solidarity and reducing inequalities, there are still critical points that need to be adapted by the public authorities in partnership with society for more effective changes, in order to contribute to the exercise of rights by the residents of the assisted communities.